2018
DOI: 10.3389/fendo.2018.00490
|View full text |Cite
|
Sign up to set email alerts
|

Life Under Hypoxia Lowers Blood Glucose Independently of Effects on Appetite and Body Weight in Mice

Abstract: Blood glucose and the prevalence of diabetes are lower in mountain than lowland dwellers, which could among other factors be due to reduced oxygen availability. To investigate metabolic adaptations to life under hypoxia, male mice on high fat diet (HFD) were continuously maintained at 10% O2. At variance to preceding studies, the protocol was designed to dissect direct metabolic effects from such mediated indirectly via hypoxia-induced reductions in appetite and weight gain. This was achieved by two separate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As a result, lactate, which is the primary end-product of anaerobic glycolysis and can be directly metabolized by certain cell types, is significantly elevated under these conditions. Other examples include alterations in carbohydrate metabolism (e.g., glucose, glycogen, and insulin-regulated pathways), which are inconsistently impacted by hypoxia in both hypoxia-tolerant and hypoxia-intolerant species [12][13][14][15], and which have major impacts on systemic function.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, lactate, which is the primary end-product of anaerobic glycolysis and can be directly metabolized by certain cell types, is significantly elevated under these conditions. Other examples include alterations in carbohydrate metabolism (e.g., glucose, glycogen, and insulin-regulated pathways), which are inconsistently impacted by hypoxia in both hypoxia-tolerant and hypoxia-intolerant species [12][13][14][15], and which have major impacts on systemic function.…”
Section: Introductionmentioning
confidence: 99%
“…The acute drop in body weight tracked closely with a similar reduction in food consumption (Fig 2E) . Previous studies have demonstrated that paired feeding rescues hypoxia-induced weight loss (Abu Eid et al, 2018), so depressed food intake is the likely cause of the observed weight loss. Research in humans has similarly demonstrated a rapid decline in food consumption at even more moderate hypoxia conditions (Shukla et al, 2005).…”
Section: Resultsmentioning
confidence: 97%
“…Hypoxia has been shown to reduce blood glucose levels independent of diminished weight gain and although the exact mechanism is unknown, it has been speculated that growth factors may play a causal role (Abu Eid et al 2018 ). Muscarinic receptors have been implicated in the activation of cellular regulators involved in the adaptive hypoxia response (Hirota et al 2004 ) suggestive of a link between muscarinic receptors and metabolic control.…”
Section: Discussionmentioning
confidence: 99%